2011
DOI: 10.1002/pssa.201000924
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic cell lines as a sensitive layer for direct monitoring of carbon monoxide

Abstract: In the past years, whole cell gas toxicity assays have been developed in order to study the harmful effects of gaseous chemicals. Cells are incubated with nutrition medium supplemented with the gaseous substances to be tested. These methods are not feasible for the examination of toxic gases, which are insoluble in water. Carbon monoxide (CO), a poorly soluble and toxic gas (lethal dose 1 vol% for some minutes) has been chosen as a model gas. Besides its binding to hemoglobin, it also leads to an inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…The gas exposure measurement procedure differs from the measurements of solved acetone and were performed as described previously in detail (Bohrn et al 2011a). The metabolic sensor chips, covered with a confluent cell monolayer and 200 ml RM, are inserted in the biomodules of the 2500 analyzing system and connected to the reference electrode and the pumping system via the perfusion head.…”
Section: Gas Exposure Device and Gas Exposure Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas exposure measurement procedure differs from the measurements of solved acetone and were performed as described previously in detail (Bohrn et al 2011a). The metabolic sensor chips, covered with a confluent cell monolayer and 200 ml RM, are inserted in the biomodules of the 2500 analyzing system and connected to the reference electrode and the pumping system via the perfusion head.…”
Section: Gas Exposure Device and Gas Exposure Measurementsmentioning
confidence: 99%
“…1) which guides the gas stream over the cells to get it in contact with the cellular membrane via diffusion. Former studies (Bohrn et al 2010(Bohrn et al , 2011a demonstrated that exposure durations of 10-15 min are sufficient to generate detectable changes in the cellular signals, while the cells still rest on the sensor surface without being mechanically detached. For all experiments, reference measurements have to be done to compare the effects of the acetone gas with the influence of non-irritant humidified synthetic air.…”
Section: Gas Exposure Device and Gas Exposure Measurementsmentioning
confidence: 99%
“…The use of cell-based sensors has increased in the last few years [17]. Important areas of research are the toxicity monitoring in aquatic environments [18,19] and also the monitoring of toxic gaseous compounds in the air, which came into the focus of cell-based sensor research [20]. One of the main reasons for the recent success is the development of cellbased sensor systems which can be used in field applications [21].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, this system was primarily used for the detection of toxic substances in liquid medium. For this work, we adapted the system as reported earlier [40], so that it can be also used for the direct exposition of the mammalian cells with toxic substances in gas phases. A direct air-cell contact was generated by drainage of the liquid medium, thereby eliminating the possibility that gas molecules will be altered before contacting the cells [41].…”
Section: Introductionmentioning
confidence: 99%